The metamorphosis and other stories - Kafka, Franz, 1883-1924.; Baker, Jason (New York : Barnes & Noble Classics, 2003)
A collection of short fiction stories by Czechoslovakian author Franz Kafka, i.
Metamorphosis -- The Great Wall of Chine -- Investigations of a dog -- The Burrow -- In the Panel Settlement -- The Giant Mole.
Translated from the German.
Adult.
Keywords: Kafka, Franz, -- 1883-1924 -- Translations into English; Kafka, Franz, -- 1883-1924.; Short stories; Short stories